Meeting employers’ and students’ expectations through the use of employment demand ontology in curriculum development - Smalberger, Chamonix (IEEE, 2011)
It has become evident in recent times that curriculums do not sufficiently cover the expected employment skill needs of graduates to be job ready directly post obtaining their qualifications. In order to assure an appropriately trained and job ready graduate workforce, it is imperative that employer expectations are incorporated into curriculums offered to students who are hoping to be trained for professional advancement. Current data gathering methods of employer expectations are time, cost and labour intensive resulting in missmatched skill sets for graduates. This paper introduces employer demand ontology currently being developed which will enable employer demand expectations to be accurately and continuously identified and incorporated into specific curricula through the use of artificial intelligence.